Parenting Programs Supporting Parents of Children with Special Needs: Program Pendampingan Orang Tua untuk Anak dengan Kebutuhan Khusus - Astuti, Wahyu Lestari; Sukinah (Indonesian Journal of Innovation Studies, 2025)
General background: Children with special needs often face stigma and exclusion, both in society and within their own families, which affects their development and parental well-being. Specific background: In Suka Rahmat Village, East Kutai Regency, many parents struggle with limited knowledge and skills in supporting their children’s growth, leading to delayed detection, inappropriate parenting, and emotional stress. Knowledge gap: While parenting programs have been widely studied, little attention has been given to village-level, cross-sectoral collaborations in strengthening parental competence. Aims: This study investigates the influence of parenting programs on improving parents’ acceptance, understanding, and skills in handling children with special needs, as well as the supporting and inhibiting factors of program implementation. Results: Using qualitative descriptive methods with interviews, observations, and documentation, findings reveal that parenting programs foster parental acceptance through honesty, patience, and therapeutic efforts, while enhancing skills in early detection, child stimulation, emotional regulation, and confidence-building. Supporting factors include cross-sectoral collaboration and parental involvement, while challenges stem from limited resources and varying parental awareness. Novelty: The study uniquely highlights the role of cross-sectoral collaboration at the village level in parenting interventions. Implications: These results emphasize the importance of sustainable parenting programs as a community-based strategy to create inclusive, adaptive, and child-centered care for children with special needs.Highlight : Parenting programs improve parents’ acceptance, skills, and confidence in handling children with special needs. Supporting factors include cross-sector collaboration, active parental involvement, and program continuity. Inhibiting factors are limited resources and varying parental understanding. Keywords : Parenting Program, Parental Acceptance, Parental Skills, Children With Special Needs, Cross-Sector Collaboration